Pharmacokinetic Differences of Grape Seed Procyanidins According to the Gavage Administration Between Normal Rats and Alzheimer's Disease Rats - Cheng, Xinhui; Zhang, Jingying; Jing, Huiting; Qi, Yu; Yan, Tingxu; Wu, Bo; Du, Yiyang; Xiao, Feng; Jia, Ying (Current Pharmaceutical Analysis, 2021)
Background: Grape Seed Procyanidins (GSP) refers to a type of natural polyphenols that have to roust antioxidant capacity. Studies have shed light on the fact that GSP significantly impacts the alleviation of Alzheimer's Disease (AD). Objective: This study aimed at investigating whether there exists a pharmacokinetics difference in GSP between normal and AD rats, a rapid UPLC-MS/MS methodology, for the detection of its content in plasma samples was put forward. We carried out an analysis of the plasma concentrations of procyanidin B2, procyanidin B3, catechin and epicatechin in normal and AD rats over time for determining the plasma concentration of GSP. Methods: We made use of 400 μL of methanol for the protein precipitation solvent in the plasma treatment. The chromatographic separation was carried out on a C18 column at a temperature of 20 °C. The mobile phase was a gradient of 0.1% formic acid in water and methanol within 15 min. Results: In the current research work, the plasma concentrations of procyanidin B2, procyanidin B3, catechin and epicatechin in AD rats were significantly higher as compared with those in normal rats (P < 0.05) and the content of epicatechin constituted the highest as compared with catechin, procyanidin B2 and procyanidin B3 following the administration of GSP. Conclusion: We discovered the better absorptions of these analytes in the AD group as compared with that in the normal group, providing an analytical basis for treating the AD with procyanidins.
Keywords: gavage administration